Kinetics and improvement of biodiesel oxidative stability by a natural antioxidant from Brucea Javanica seeds / Khalilullah - Khalilullah, - (2015)

(untitled)
The study was conducted to determine antioxidant activity of Brucea javanica seed and test its potential to be used as natural antioxidant for biodiesel. 2, 2-diphenyl-1-picrylhydrazyl (DPPH), Ferric Reducing antioxidant Power (FRAP) and Metal Chelating Assay are the methodologies used to test antioxidant activity. The results indicated that higher flavonoids and phenolic contents could be detected in ethyl acetate and methanol extracts as compared to hexane extract. Ethyl acetate extract of B.javanica seed showed highest DPPH inhibition activity up to 90% with (IC50= 31.2 g/ml). On the other hand, methanol extract had a highest FRAP activity (0.180 ±0.03 mmol Fe2+ /g extract) with 71% inhibition. In the metal chelating assay, ethyl acetate extract indicated the highest chelating activity with 59% inhibition (IC50=299 g/ml). In addition, the bioactive compounds were also analysed using LCMS and GCMS for confirmation. The chemical compounds found in B. javanica seed extract were brevifolin, ellagic acid, gallic acid, quinic acid, strictinin, O-methyl ellagic acid, protocatechuic acid and ellagic acid isomers from LCMS analyses. 35 chemical have been identified in GCMS analyses. In order to confirm anti-oxidation effect of B. javanica seed extract, rancimat and thermal oxidation tests were performed at 110oC and 80oC respectively. For rancimat test, Gallic acid showed the highest oxidative stability of biodiesel up to 69 hours induction period (IP). However, on the other end, ethyl acetate crude extract at 1000 ppm suggested better stability up to 6h in thermal oxidation test. While, kinetics evaluation showed a high degree of correlation coefficient (R2 =0.9) confirming that the degradation of antioxidant in improving oxidative stability of biodiesel follows first order kinetics.